PERSEN DEGRADASI EKSTRAK ETANOL KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) SELAMA PENYIMPANAN THE PERCENTAGE OF ETHANOL EXTRACTS OF ROSELLE PETALS (Hibiscus sabdariffa L.) DURING STORAGE - firmasari firmasari; Ni Ketut Sumarni; Ruslan; Hardi Ys (KOVALEN: Jurnal Riset Kimia, 2019)
Ethanol extract of roselle petals (Hibiscus sabdariffa L.) is more stable in low pH than in high pH. The research aims to monitor and determine the effect of ratio content in ethanol extract of roselle petals (Hibiscus sabdariffa L.) in tomato sauce and the pH effect on the percentage of ethanol extract degradation during storage. Two independent variables implemented in this study, are ratio content of ethanol extract of roselle petals (Hibiscus sabdariffa L.) in tomato sauce and pH. Ethanol extract of roselle petals (Hibiscus sabdariffa L.) in tomato sauce with ratio content 0,5:1; 1:1; and 1:0 (w/w) and adjusted to pH 2, pH 3, pH 4, pH 5 and pH 6, respectively were investigated. The absorbance measurement of Ethanol extract of roselle petals (Hibiscus sabdariffa L.) in tomato sauce was depend on each treatment, then analyzed using completely randomized design. The percentage of ethanol extract of roselle petals (Hibiscus sabdariffa L.) degradation in tomato sauce decreased in ratio content 1:0 (w/w) at pH 2 with percentage content of degradation is 30.09%. Furthermore, after 10 days of storage, the highest percentage of ethanol extract of roselle petals (Hibiscus sabdariffa L.) in tomato sauce degradation is 93.33% with ratio content is 0.5:1 at pH 6 and the lowest is 30.09% with ratio content 1:0 at pH 2. Keywords: Roselle petals, Ethanol Extract, Tomato Sauce, Percentage of Degradation